Mathematical models and pilot studies of antennas of the onboard equipment of system of video control of spacecrafts and accelerating blocks - D.S. Klyuev; S.B. Philippov; A.S. Maltcev; V.A. Neganov (Физика волновых процессов и радиотехнические системы, 2017)
Article is devoted to creation of mathematical models and experimental working off of electric characteristics of antennas of the onboard equipment of video control of spacecrafts and accelerating blocks. Creation of mathematical models is carried out in HFSS on the basis of integral representations of the electromagnetic field. The question of optimization between the sizes of the antenna and the necessary direction characteristic with the decimeter L-wave range is considered. Results of numerical modeling and experimental datas for two samples of antennas are given.